Floating-Gate Nonvolatile Memory With Ultrathin 5-nm Tunnel Oxide - Paulsen, Ron (IEEE Transactions on Electron Devices, 2008)
Reliability results of floating-gate (FG) memory using 5-nm tunnel oxides in mature (0.25 mum) to advanced (65 nm) logic processes from multiple foundries are reported. Good intrinsic retention is seen across the process nodes studied and for gate oxides as thin as 4.8 nm. With differential memory cells, we also demonstrate promising reliability results with respect to program-cycle-induced tail bits. We conclude that it is possible to develop a small-bit-count FG nonvolatile memory (NVM) array using 5-nm oxide, enabling embedded logic NVM in advanced CMOS processes with no additional masks or processing steps.